Business-to-Business (B2B) Marketing for Industrial Products in Google Ads: Strategies, Challenges, and Effectiveness - Ruvi, Mohammad (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
This study explores the potential of Google Ads in Business-to-Business (B2B) marketing, focusing on its effectiveness, challenges, and success factors in the industrial sector, particularly for products such as pumps, valves, and compressors. The research originality lies in its comprehensive analysis of both the technical and socio-economic barriers to Google Ads adoption, filling gaps in the existing literature regarding long-term ROI and regional variations in campaign effectiveness. The study employs a mixed-methods approach, combining a systematic literature review, case studies of successful B2B Google Ads campaigns, and semi-structured interviews with industry experts. Empirical results reveal that Google Ads is highly effective for lead generation and brand awareness, with tailored campaigns achieving an average conversion rate of 8.5%. However, challenges such as high cost-per-click (CPC), complex buyer journeys, and ad fatigue hinder campaign success. Key success factors include data-driven optimization, integration with other marketing channels, and the use of industry-specific keywords. The findings have significant implications for B2B marketers, emphasizing the need for strategic budget allocation, continuous campaign optimization, and policy frameworks that support digital marketing adoption. This research provides actionable insights for businesses aiming to leverage Google Ads to enhance competitiveness in the digital marketplace.